Using a GIS-based floating catchment method to assess the provision of library services within proximity of Quezon City Public Library branches - Yague, Clifford A.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
The study explored the variations on accessibility to the library services provided by the Quezon City Public Library (QCPL) system in relation to potential population demand, using a GIS-based accessibility model. How are the library services of the QCPL branch libraries distributed in relation to the potential population demand? Are they able to provide equal access to information services across the Quezon City area?
Findings show that most of the barangays in Quezon City need to travel between 1000 to 2000 meters to reach the nearest QCPL branch. District 4 was found to have the shortest average travel distance from barangay to library, while District 2 and 6 had the longest average travel distances.
The study also found that 21.83% or 31 of the barangays in Quezon City have no access to a QCPL branch within 2000 m of travel distance. Though it may seem low, these barangays make up 45% of the entire population of Quezon City. District 3 had the highest average number of libraries within proximity, while District 2 had the lowest average followed by District 5 and 6.
The results of the study indicated that access to the QCPL branches is higher for District 1, 3 and 4, which compose the southern half of Quezon City. And low access to the QCPL branches for District 2, 5 and 6, which compose the northern half of the city.
Thesis (Bachelor of Library and Information Science)
Keywords: Geographic information systems -- Philippines -- Quezon City